Management of the Center for Early Childhood Education Development in Improving the Quality of Early Childhood Education in Jambi Province - Mukhtar, Mukhtar; Hidayat, Hidayat; Duyardin, Duyardin (Yayasan Sembilan Pemuda Indonesia, 2020)
This study determined 1) why the Jambi Province Early Childhood Education and Community Education have not been able to improve the quality of Early Childhood Education; 2) how is the management of the Jambi Province Early Childhood Education and Community Education Partnership in improving the quality of Early Childhood Education; 3) how is the quality improvement by Jambi Province Early Childhood Education and Community Education in Jambi Province; 4) how to manage Jambi Province Early Childhood Education and Community Education to improve the quality of Early Childhood Education. This research used descriptive qualitative method, with a phenomenological-naturalistic approach. Sampling was taken by purposive sampling. The results showed that Jambi Province Early Childhood Education and Community Education Jambi Province have implemented management to improve the quality of Early Childhood Education in Jambi by implementing quality management starting from planning, organizing, implementing and monitoring which refers to TQM in Education, but in the process and the results were not optimal and not yet able to provide consumer’s satisfaction.